Analysis of Creep in Paperboard Packages With Plastic Tops - Arvidsson,Jakob; Grönvall,Jesper (2004)
Beverage packages made of paper and plastic materials that are stored for a long time, deform due to creep deformations. The phenomena is termed bulging and means that the package changes its shape. Bulging is a major issue for the producers of beverage packages. The purpose of this master’s dissertation, is to develop a Finite Element-model for simulation of bulging of beverage packages at varying loadings and time scales that is veriﬁed to experimentally determined data of creep. In order to formulate a suitable FE-model for simulation of creep, a profound knowledge of the material behavior of the various materials in a beverage package is required. Therefore, creep tests of paper, polymer, and aluminum foil were performed. The creep deformation of paper was found to be approximately four to six times larger in CD than in MD. The elastic + creep deformation of the laminate is approximately three times larger in CD in comparison to MD. A creep material model for each of the materials in the laminate was calibrated to experimental data. The creep behavior of the FE-model was compared to bulge tests, which described the deﬂection of the package. The FE-model was proven to produce accurate results for shorter time periods and acceptable results for longer time frames. As experimental creep tests require long time frames, it is important to anticipate the creep behavior with a mathematical model. The FE-method was shown to be an excellent tool in order to describe, understand, and predict the phenomena of creep.
Keywords: Creep; beverage package; paper properties; FEM; ABAQUS; Power-law; crease